في تعليم مهارة الكلام باستخدام مدوّنة الفيديو في المدرسة الثانوية الحكمة فورووأسري ( 4c) تحليل - العلم, حريص (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2023)
4c skills are important things that students must have in the 21st century, including in speaking Arabic learning. One media that is suitable for use in Maharah Kalam learning and is popular in the 21st century is vlog. This research discusses the analysis of 4c skills in speaking Arabic learning using vlogs for MA Al-Hikmah Purwoasri students. The research method uses a qualitative approach with analytical descriptive studies. The results of the research are that 4C skills are applied quite well. The statement is; 1) Communication, seen in good wording and listening attitude. 2) Collaboration is seen through discussion, compromising, showing respect, and helping each other. 3) Critical thinking is seen through activities of testing the truth of statements, distinguishing relevant information, and making solutions. 4) Creativity is seen in curiosity, flexibility and originality of ideas. Apart from that, this learning model also makes students and teachers more active and innovative and not conservative. تعد مهارات 4C من الأشياء المهمة التي يجب أن يتمتع بها الطلاب في القرن الحادي والعشرين، بما في ذلك تعليم مهارة الكلام. إحدى الوسائط المناسبة للإستخدام في تعليم مهارة الكلام والمعروفة في القرن الحادي والعشرين هي مدونة الفيديو. يناقش هذا البحث تحليل مهارات 4C في تعليم مهارة الكلام باستخدام مدونة الفيديو لطلاب المدرسة الثانوية الحكمة فورووأسري. يستخدم طريقة البحث المنهج النوعي مع الدراسات الوصفية التحليلية. نتائج البحث هي أن مهارات 4C يتم تطبيقها بشكل جيد في التعليم. وبيانه هو؛ 1) التواصل، والذي يظهر في صياغة واضحة وحسن الإستماع. 2) يظهر التعاون من خلال المناقشة والتسوية وإظهار الإحترام ومساعدة بعضنا البعض. 3) يظهر التفكير النقدي من خلال أنشطة اختبار صحة العبارات، وتمييز المعلومات ذات الصلة، وإيجاد الحلول. 4) يتجلى الإبداع في الفضول والمُرُونَة وأصالة الأفكار. وبصرف النظر عن ذلك، فإن نموذج التعلم هذا يجعل الطلاب والمعلمين أكثر نشاطًا وابتكارًا وليس محافظين.